Managing Secondary Education in Nigeria for National Cohesion - Anthony Ossai (dialektika kontemporer, 2023)
Globally, a major purpose that education has been identified to attain is national cohesion. Unarguably, certain essential leadership and administrative skills are required of the principals, who are the managers of the secondary education system, if secondary education will achieve national cohesion. Therefore, this study looked at the relationship between effective management of secondary education and the attainment of national cohesion in Nigeria. The paper looked at the concept of management and explored the state Nigerian educational system with an emphasis on secondary education. It attained the concept of secondary education and the goals and challenges of secondary education. The paper also discussed the concept and challenges of national cohesion, as well as education and national cohesion. The paper concluded that secondary education managers should possess the necessary administrative leadership skills in order to attain national cohesion. Based on the analysis and conclusion, the paper recommended, among others, that Nigeria should devote 26% of the national budget to education, policy management and systems should provide guidance and coordination to ensure effective and institutionalised educational responses to national challenges, and educational content, curriculum, and materials should emphasise value clarification, capacity development, and skill building.